Decolorization of textile dye by Candida albicans isolated from industrial effluents - Vitor, Vivian [UNESP]; Corso, Carlos Renato [UNESP] (Springer Heidelberg, 2008)
The aim of the present work was to observe microbial decolorization and biodegradation of the Direct Violet 51 azo dye by Candida albicans isolated from industrial effluents and study the metabolites formed after degradation. C. albicans was used in the removal of the dye in order to further biosorption and biodegradation at different pH values in aqueous solutions. A comparative study of biodegradation analysis was carried out using UV-vis and FTIR spectroscopy, which revealed significant changes in peak positions when compared to the dye spectrum. Theses changes in dye structure appeared after 72 h at pH 2.50; after 240 h at pH 4.50; and after 280 h at pH 6.50, indicating the different by-products formed during the biodegradation process. Hence, the yeast C. albicans was able to remove the color substance, demonstrating a potential enzymatic capacity to modify the chemical structure of pigments found in industrial effluents.
Keywords: Textile dyes; Biodegradation; Decolorization; Candida albicans; Direct Violet 51; Biosorption